Sensitivity enhancement of Si-29 double-quantum dipolar recoupling spectroscopy by Carr-Purcell-Meiboom-Gill acquisition method - Goswami, M.; Madhu, Perunthiruthy K.; Dittmer, J.; Nielsen, N. C.; Ganapathy, Subramanian (Chemical Physics Letters, 2009)
An enhancement in the detection sensitivity of dipolar recoupled Si-29 double-quantum magic-angle spinning experiment is shown with a Carr-Purcell-Meiboom-Gill (CPMG) train of pi pulses during the acquisition period. Symmetry-adapted pulse schemes, such as POST-C7 and SR26(4)(11), are used for the double-quantum excitation. Application of POST-C7-CPMG method for framework characterisation is demonstrated in the disordered and catalytically important ZSM-5 molecular sieve. Based on the observed double-quantum dipole-dipole correlations and the known T-site Si connectivities, the assignment of all the signals is made for the orthorhombic phase of the as-synthesised (CN form) material. (C) 2009 Elsevier B. V. All rights reserved.

SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures